epresentações sociais da aprendizagem docente de professores universitários em suas trajetórias de formação - Ana Claudia Lopes Chequer Saraiva (2005)
This thesis has its foundation in the study of social representations of the teaching learning process of university professors from the Pedagogy, Law and Mathematics programs. Formation and acting area were the variables considered. The objective was to identify the socio-educational spaces, experiences, processes and interlocutors which integrate themselves in their personal trajectories in the ambit of the teaching learning process besides the analysis of the relation between the professors representation and the disciplinary epistemological directions which give them foundation in their areas of formation and professional performance. We interviewed all the professors from the mentioned programs of a Federal University of Minas Gerais. We used as instruments the free association technique and hierarchical choices and interviews. In the first case, it was applied the statistical analysis for the evaluation of the group words with the highest frequency and hierarchy; In the second, the analysis of the contents, in which the transcribed passages were cut out, and we considered the following categories: concept, processes, relevance, meaningful experiences. The final results showed that the professors anchored their social representations of the teaching learning process in the values that constitute their professional formation fields. In the Pedagogy program, the humanistic, the historical, and the political aspects are pointed out; in the Law program, the humanistic, the methodological and the empirical features are stressed; and in the Math course, the methodological and the empirical ones are pointed out.